DAJJAL DALAM PERSPEKTIF HADIS (ANALISIS HADIS TENTANG DAJJAL DALAM KITAB SUNAN IBNU MAJAH) - Halim, Abdul; Rambe, Uqbatul Khoir; Hidayat, Muhammad Sofian (SHAHIH (Jurnal Ilmu Kewahyuan), 2020)
The purpose of this research is to examine and analyze the opinion of Ibn Majah regarding the Dajjal in his Hadith book Sunan Ibn Majah . The analysis technique used by researchers is library research. The hadiths collected in this research were obtained using the maudu'i method. The data that has been collected are then described using a historical approach, then analyzed using the content analysis method. The results show, 1) In his book, Ibn Majah mentions that the Dajjal is also called a liar, because he obeys the truth with his falsehood. 2) The opinion of Ulama regarding The hadiths related to the Dajjal in the book of Sunan Ibn Majah are not very different, because the Dajjal itself has been described by the Prophet Muhammad in several narrations . 3) In hadith book Sunan Ibn Majah, there are 15 hadith related to the Dajjal, in which there is a discussion of the physical characteristics of the Dajjal, the time when the Dajjal comes out, the place where the Dajjal comes out, the Dajjal’s followers, the Dajjal's actions, and the death of the Dajjal, as well as prayers and practices that can avoid from the liar of the Dajjal.